The effects of Shenkang suppository on kidney function and gut microbiota in nondialysis patients with chronic kidney disease stages 3–4: A randomized controlled trial - Zhang, Weiwei; Zhang, Xin; Xu, Shuang; Waheed, Yousuf Abdulkarim; Xu, Yizhou; Li, Shulin; Sun, Dong (Frontiers in Pharmacology, 2025)
BackgroundChronic kidney disease (CKD) patients have high prevalence and mortality rates; however, current treatment options remain limited. The Shenkang suppository (SKS) is a traditional Chinese medicine used in the clinical management of CKD. Increasing evidence suggests a close relationship between the gut microbiome and CKD. We aimed to investigate the impact of SKS on kidney function and the gut microbiota in CKD stage 3–4 patients.MethodsIt’s a single-center randomized controlled trial (n = 80). CKD stage 3–4 patients were randomly assigned at a 1:1 ratio to either the control group (n = 40) or the SKS group (n = 40) and followed for 8 weeks. Baseline data, clinical indicators, kidney markers, and stool samples were obtained from participants before and after treatment. The bacterial DNA was isolated from fecal samples and analyzed via high-throughput 16S rRNA sequencing.ResultsA total of 34 patients in the SKS group and 36 in the control group completed the study. Kidney function in the control group significantly worsened after 8 weeks (P < 0.05), whereas SKS had a positive effect on slowing the progression of kidney function decline. After 8 weeks of SKS intervention, the beneficial bacteria Coriobacteriaceae and Ruminococcaceae-Ruminococcus proliferated dramatically, whereas the abundance of the harmful bacteria Veillonellaceae decreased. Linear discriminant analysis (LDA) revealed that SKS treatment increased the proportion of Streptococcus and decreased the proportions of Planctomycetes, Spirochaetes, Rhodocyclales, Actinomycetaceae, Veillonellaceae, and Dechloromonas. These changes were not observed in the control group. Correlation analysis revealed a negative association between Bifidobacterium, Blautia, Enterococcaceae_Enterococcus, and clinical kidney function indicators, whereas Parabacteroides, Acinetobacter, Sutterella, Oscillospira, and Alistipes were positively correlated with kidney function.ConclusionSKS could delay the progression of kidney function in CKD stage 3–4 patients, possibly by modulating the dysbiosis of the gut microbiota. The close associations between certain gut microbiota and clinical kidney function indicators suggest that the gut microbiota could serve as a new therapeutic target for CKD.Clinical Trial Registrationhttps://www.chictr.org.cn/, Chinese Clinical Trial Registry Identifier: ChiCTR2200058493.